Comparison of surgical cricothyroidotomy training: a randomized controlled trial of a swine model versus an animated robotic manikin model. Issue 1 (26th April 2020) - Pandian, Vinciya; Leeper, William Robert; Jones, Christian; Pugh, Kristy; Yenokyan, Gayane; Bowyer, Mark; Haut, Elliott R
Abstract : Background: Airway obstruction remains a preventable cause of death on the battlefield. Surgical cricothyroidotomy is an essential skill for immediate airway management in trauma. Training for surgical cricothyroidotomy has been undertaken using simulators, cadavers or animal models. The ideal approach to training for this low volume and high-risk procedure is unknown. We hypothesized that current simulation technology provides an equal or better education for surgical cricothyroidotomy when compared with animal tissue training. Methods: We performed a prospective randomized controlled study comparing training for surgical cricothyroidotomy using hands-on training on swine versus inanimate manikin. We enrolled medical students who had never performed or had formal instruction on surgical cricothyroidotomy. We randomized their instruction to use either a swine model or the inanimate version of the Operative Experience Inc. advanced surgical manikin. Participants' skills were then evaluated on human cadavers and on an advanced robotic manikin. Tests were scored using checklists modified from Objective Structured Assessment of Technical Skills and Tactical Combat Casualty Care. We compared scores between the groups using Wilcoxon rank sum tests and generalized linear models. Results: Forty-eight participants were enrolled and trained; 30 participants completed the first testing session; 25 completed the second testing session. The mean time to establish an airway from the incision until the cuff was blown up was 95±52 s. There were no significant differences in any of the outcome measures between the two training groups. Discussion: Measured performance was not different between subjects trained to perform surgical cricothyroidotomy on an animal model or a high fidelity manikin. The use of an advanced simulator has the potential to replace live tissue for this procedure mitigating concerns over animal rights. Levels of evidence: I